Birokrasi Menghadapi Perubahan Lingkungan - Dyah Ratih (Magister Ilmu Administrasi Publik, 2000)
The availability of professional apparatur is expected to anticipate the very fast changing environment. The changing environment requires the capability of apparatus to grasp opportunities in order to optimize economic growth sustainably. However, professionalism can only be achieved if there is political will from the government to change the philosophy, value, structure and procedure of bureaucracy. In the case of tourism, new approaches are essential to develop the performance of tourism compatible with market. However, we still have to maintain socio-cultural aspects which are the main factor of tourism.